2016
DOI: 10.1371/journal.pone.0155102
|View full text |Cite
|
Sign up to set email alerts
|

Quantified Mechanical Properties of the Deltoid Muscle Using the Shear Wave Elastography: Potential Implications for Reverse Shoulder Arthroplasty

Abstract: The deltoid muscle plays a critical role in the biomechanics of shoulders undergoing reverse shoulder arthroplasty (RSA). However, both pre- and postoperative assessment of the deltoid muscle quality still remains challenging. The purposes of this study were to establish a novel methodology of shear wave elastography (SWE) to quantify the mechanical properties of the deltoid muscle, and to investigate the reliability of this technique using cadaveric shoulders for the purpose of RSA. Eight fresh-frozen cadaver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 35 publications
2
36
0
2
Order By: Relevance
“…Haizlip et al [21] showed that collagen and elastin architectures of muscle bers mainly determined MD elasticity, which may vary between different gender. It is also well con rmed that histologic changes in muscle structure could affect increased muscle strain [22][23][24][25]. However, there are not obvious difference at shoulder 90° abduction.…”
Section: Discussionmentioning
confidence: 93%
“…Haizlip et al [21] showed that collagen and elastin architectures of muscle bers mainly determined MD elasticity, which may vary between different gender. It is also well con rmed that histologic changes in muscle structure could affect increased muscle strain [22][23][24][25]. However, there are not obvious difference at shoulder 90° abduction.…”
Section: Discussionmentioning
confidence: 93%
“…With such complex anatomy, it is not possible to define only one fibre direction and to define the orientation of the ultrasound probe accordingly (Hatta et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…The technique is fast, convenient and applicable to a variety of clinical scenarios in which other approaches would potentially be inadequate; thus, it has been used successfully for breast cancers diagnosis (Athanasiou et al, 2010) and liver fibrosis staging (Ferraioli et al, 2014). In addition, quantitative assessments of the mechanical properties of skeletal muscles have also been investigated in in-vivo and in-vitr o studies (Akagi et al, 2015; Hatta et al, 2016a; Hirata et al, 2015; Hug et al, 2013). …”
Section: Introductionmentioning
confidence: 99%